SOSIALISASI UNDANG-UNDANG HARMONISASI PERPAJAKAN BAGI PELAKU INDUSTRI KECIL MENENGAH KABUPATEN MAGETAN - Dian Wahyudin; Indriani Rahayuningtyas; Faizah Julina (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
To maximize tax revenue, in 2021 the Government will reform tax regulations by issuing the Law on Harmonization of Tax Regulations (UU HPP). One of the main points of reforming the regulations in the HPP Law is to provide convenience and simplification of tax administration facilities for Micro, Small and Medium Enterprises (MSMEs) which have a business turnover in one tax year of not more than Rp. 4,800,000,000 (four billion eight hundred million). rupiah). These facilities include a Final Income Tax (PPh) rate of 0.5% of gross turnover and a limit of non-taxable gross income of up to Rp500,000,000 (five hundred million rupiah) per year. Based on the results of interviews conducted by the PkM team to Small and Medium Industries in Magetan Regency, it was found that IKM actors did not know about the HPP Law. The PkM method in this activity is to carry out theoretical socialization and provide solutions related to tax problems faced. Partners of this service activity are 30 IKM Magetan Regency. As a result of this PkM, the IKMs know the HPP Law related to MSMEs, are able to calculate, deposit and report taxes, which has an impact on increasing tax revenues in Magetan Regency.